Exploring the police response to technology-driven changes in online child sexual exploitation offending - Harmson-Silvestri, Michael (2024)
This thesis explores the digital and social media knowledge and training of police officers who investigate online Child Sexual Exploitation Material (CSEM) offending. The training and digital and social media knowledge of those who work within online sexual crime investigation have been largely overlooked. When exploring online CSEM offending, current and existing literature has often focused on police cybercrime investigation overall, including fraud, harassment and stalking. Appropriately, this thesis attempts to fill some of the gaps in the knowledge regarding police training related to online CSEM investigation and recommendations for future policy and practice. The study employs a constructionist ontological position and an interpretivist epistemology using a convergent mixed-method approach. The study involves two stages. Stage one of this study is comprised of semi-structured interviews with front-line police officers and civilian staff working within online sexual crimes investigation. In total, 11 participants were interviewed. Data were collected and then transcribed using approved university transcription software. The data were then coded and analysed using a process of thematic analysis. During stage two, quantitative data were explored using existing data from the Internet Watch Foundation. The data were coded and analysed using a thematic analysis of specific themes related to online CSEM offending and the risk to children. The resultant findings suggest that the training and knowledge of police officers working in online sexual crime investigations are inconsistent with the serious nature of their roles and responsibilities. Other findings suggest that there is a need for police leadership to adopt learning theories to enable policing organisations to retain and share knowledge with academics and practitioners on new offending behaviours identified. Additionally, there is a need for formal accreditation for officers working in online CSEM investigations and a consistent approach to their training and knowledge sharing. Officers working in online CSEM investigation also have a responsibility to engage in self-directed learning and continuing personal development regarding new knowledge related to the changing nature of social media and the digital platforms used for online CSEM offending.